새로운 날개단면을 이용한 KD-프로펠러 씨리즈 개발 - 이진태(J. T. Lee); 김문찬(M. C. Kim); 안종우(J. W. Ahn); 김호충(H. C. Kim) (大韓造船學會 論文集, 1991)
A new propeller series is developed using the newly developed blade section(KH18 section) which behaves better cavitation characteristics and higher lift-drag ratio at wide range of angle-of-attack. The pitch and camber distributions are disigned in order to have the same radial and chordwise loading distribution with the selected circumferentially averaged wake input. Since the geometries of the series propeller, such as chord length, thickness, skew and rate distribations, are selected by regression of the recent full scale propeller geometric data, the performance prediction of a propeller at preliminary design stage can be mure realistic. Number of blades of the series propellers is 4 and the expanded blade area ratios are 0.3, 0.45, 0.6 and 0.75. Mean pitch ratios are selected as 0.5, 0.65, 0.8, 0.75 and 1.1 for each expanded area ratio. The new propeller series is composed of 20 propellers and is named as KD(KRISO-DAEWOO) propeller series. Propeller open water tests are performed at the experimental towing tank, and the cavitation observation tests and fluctuating pressure measurements are carried out at the cavitation tunnel of KRISO. $B_{P}-δ$ curves, which can be used to select the optimum propeller diameter at the preliminary design stage, are derived from a regression analysis of the propeller often water test results. The KD-cavitation chart is derived from the cavitation observation test results by choosing the local maximum lift coefficient and the local cavitation number as parameters. The caviy extent of a propeller can be predicted more accurately by using the KD-cavitation chart at a preliminary design stage, since it is derived from the results of the cavitation observation tests in the selected ship's wake, whereas the existing cavitation charts, such as the Burrill's cavitation chart, are derived from the test results in uniform flow. 캐비테이션 특성이 우수하고 넓은 받음각에서 양력-향력비가 큰 새로운 날개단면(KH18 단면)을 사용하여 체계적인 방법으로 기하학적 형상을 변화시켜 설계된 새로운 계열 프로펠러의 개발을 시도하였다. 새로운 계열 프로펠러의 형상을 설계함에 있어 기존의 계열 프로펠러와는 달리 선택된 반류분포의 회전방향 평균 반류분포를 입력자료로 하여 반경방향 부하분포와 코오드 방향 부하분포를 동일하게 유지하면서 피치 및 캠버의 형상을 결정하였다. 또한 코오드 길이, 두께, 스큐 및 레이크 분포와 같은 형상은 최근 실적선 프로펠러의 형상 특성을 정형화하여 선택되었기 때문에 초기설계시 설계된 형상이 최종 설계 프로펠러의 형상과 크게 다르지 않을 것으로 생각되어 초기성능을 보다 정확하게 추정할 수 있게 하였다. 설계된 계열 프로펠러는 날개수 4개인 프로펠러를 대상으로 날개 전개면적비 4개($A_{E}/A_{O}$=0.3, 0.45, 0.6, 0.75)에 대하여 각 전개면적비에서 평균피치비를 5개(P/D=0.5, 0.65, 0.8, 0.95, 1.1)로 변화시켜 총 20개의 프로펠러로 구성되었으며 KD-프로펠러 씨리즈(KRISO-DAEWOO Propeller Series)라 명명하였다. 설계된 계열 프로펠러들에 대하여 단독특성시험, 캐비테이션 관찰시험, 변동압력 계측시험을 수행하였다. 프로펠러 단독특성 시험결과의 회귀해석결과로 부터 $B_{P}-δ$ 곡선을 도출하여 초기설계 단계에서 최적 프로펠러 직경등을 쉽게 결정할 수 있게 하였다. 기준으로 선택된 반류분포(2700TEU 콘테이너선의 반류) 후류에서 프로펠러 추력계수 및 캐비테이션 수를 체계적으로 변화시킨 상태에서 캐비테이션 관찰시험 및 변동압력계측시험을 수행하였다. 양력면이론에 의한 비정상 프로펠러 성능해석에 의해 계산된 최대 국부양력계수 ($C^{max}_{l,0.8R}$)와 국부캐비테이션 수(${σ}_0=\frac{p-p_v}{\frac{1}{2}{ρ}V^2_{0.8R}}$)를 기준으로 캐비테이션 관찰시험 결과를 정리하여 KD-캐비테이션 챠트를 도출하였다. 기존의 캐비테이션 챠트는 균일류중의 시험 결과를 정리하여 작성되었으나 KD-캐비테이션 챠트는 반류분포중에서 시험된 프로펠러 관찰시험 결과로 부터 도출되었으므로 초기설계 단계에서 보다 정확한 캐비테이션 발생량 추정이 가능하리라 예상된다.